Clinical Risk Score for Invasive Pulmonary Aspergillosis in Patients With Liver Failure: A Retrospective Study in Zhejiang - Zhang, Xuan; Shen, Sijia; Dai, Xiahong; Bi, Yunjiao; Zhang, Junjie; Wu, Yuhao; Shi, Yishang; Wei, Runan; Gao, Hainv (Frontiers in Medicine, 2021)
Purpose: The mortality of invasive pulmonary aspergillosis (IPA) in patients with liver failure was high. However, the prophylactic treatment in those patients with high risk factor for IPA have not been researched. Patients and methods: A multicenter, retrospective study was conducted in patients with liver failure. The study cohort of liver failure was randomly split into training set for model development and the other served as the testing set for model verification .Multivariate analysis was performed to identify the risk factors of IPA. A weighted risk score for IPA was established. Anti-fungal treatment was prophylactic used in patients with medium and high IPA risk to evaluate the effect. Results: In total, 1722 patients with liver failure were enrolled. 57 patients who received prophylactic treatment were excluded from the risk factor system study. 1665 patients were randomly split at a ratio of 2:1 into two datasets. Diabetes, glucocorticoids, plasma exchange, and hepatorenal syndrome (HRS) were risk factors for IPA in liver failure patients, with a weighted risk scores of 4, 7, 2 and 3, respectively. In the validation set and test set, The patients with risk scores of ≤3 presented low incidences of IPA at 4.0% and 2.7%. Patients with risk scores of 4 5 had an IPA incidence of 7.6% and 10.1%, and could be considered as a medium-risk group(P <0.01 vs. the group with scores of≤3). Whereas those with risk scores of >5 manifested a significantly higher IPA incidence of 21.2% and 12.7%, who were considered as a high-risk group(P<0.01 vs. the groups with scores of 4 5 and >5, respectively). The IPA risk scores in the training set and testing test were also analyzed by the ROC with an area under the ROC of 0.7152, and 0.6912. In this study, 57 patients received anti-fungal prophylaxis, the incidence of IPA was 1.8%, which was significantly lower after prophylactic anti-fungal therapy(P＜0.001). Conclusions: A weighted risk score for liver failure patients complicated with IPA was established and confirmed in testing cohort. Voriconazole prophylactic treatment to patients with liver failure with medium and high IPA risk can effectively prevent Aspergillus infection.